Manajemen Inovasi Digital melalui Aplikasi SIMAPEL: : Transformasi Budaya Kerja Guru di MANU Putra Buntet Pesantren - Wawan Shofwani; Dewi Shinta Nuriyah; Moh. Ali; Dewi Cahyani (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
The transformation of teachers' work culture has become one of the main challenges in the era of educational digitalization. Digital innovations based on management information systems (MIS) are believed to enhance work efficiency, discipline, and accountability in educational environments, including madrasahs. This study aims to explore how digital innovation management through the implementation of the Simapel application (Educational Service Management Information System) contributes to changes in the work culture of teachers at MANU Putra Buntet Pesantren. In this study, a qualitative approach with a case study design was used, involving research subjects consisting of teachers, the head of the madrasah, and Simapel application operators. Data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The research results indicate that the use of Simapel encourages a positive transformation in the teachers' work culture, particularly in terms of discipline, punctuality in reporting, more structured work communication, and increased digital literacy. Madrasah management plays an important role in initiating, directing, and facilitating this digital innovation process through policies, training, and ongoing evaluation. However, challenges such as initial resistance, technical limitations, and the need to adapt remain part of the transformation process. This study concludes that digital innovation management through Simapel not only serves as an administrative tool but also as a strategic instrument in shaping a professional work culture within the madrasah environment. This study recommends the need for broader system integration, strengthening user training, and sustainable policy support in the implementation of educational SIM.